Effectiveness of cryoballoon ablation for atrial fibrillation in patients with left common pulmonary vein variant - Elias, Adi; Marai, Ibrahim; Eyal, Alon; Darawsha, Wisam; Shehadeh, Faheem; Glueck, Robert; Beinart, Roy; Nof, Eyal; Michowitz, Yoav; Glikson, Michael; Konstantino, Yuval; Haim, Moti; et al. (Heart rhythm O2, 2025)
Pulmonary vein isolation (PVI) with cryoballoon technology is widely used for rhythm control in atrial fibrillation (AF). However, there are limited data on its effectiveness in patients with the left common pulmonary vein (LCPV) variant. The study aimed to examine the outcomes of cryoballoon ablation in patients with the LCPV variant. The Israeli Catheter Ablation Registry is a prospective, multicenter cohort that included citizens who underwent PVI during the years 2019–2021. Study endpoints were acute isolation success of the pulmonary veins (PVs), AF recurrence, and the need for a repeat ablation procedure at 12 months. The study included 74 patients with the LCPV variant and 822 patients with standard PV anatomy. The acute isolation success rate of the LPVs was significantly lower in LCPV variant patients compared with those with a standard anatomy. However, there was no significant difference in the acute isolation success rate of the right PVs between the 2 groups. At 12 months, the rates of AF recurrence did not differ significantly between the LCPV variant group (17.6%) and the standard anatomy group (11.1%) (P = .09), and multivariable adjustment LCPV was not associated with AF recurrence (hazard ratio 0.86, 95% confidence interval 0.43–1.74). Similarly, the rate of repeat ablation for recurrent AF did not differ significantly. In our study, we found that isolating the LCPV using cryoballoon PVI was more challenging than isolating standard anatomy. Despite this, the effectiveness of cryoballoon ablation in patients with LCPV anatomy did not differ significantly from that in the standard anatomy group. [Display omitted]